2017
DOI: 10.1111/psyp.13023
|View full text |Cite
|
Sign up to set email alerts
|

Openness to experience and adapting to change: Cardiovascular stress habituation to change in acute stress exposure

Abstract: Underlying psychophysiological mechanisms of effect linking openness to experience to health outcomes, and particularly cardiovascular well-being, are unknown. This study examined the role of openness in the context of cardiovascular responsivity to acute psychological stress. Continuous cardiovascular response data were collected for 74 healthy young female adults across an experimental protocol, including differing counterbalanced acute stressors. Openness was measured via self-report questionnaire. Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 49 publications
6
24
0
Order By: Relevance
“…First, the current passive stress task was successful in eliciting a notable cardiovascular stress response. Furthermore, participants' psychological experience of the task (in terms of PA, perceived stress, and anxiety) was no different to their experience during a well-established active stress task (Hughes & Callinan, 2007;O'Súilleabháin et al, 2018). Second, the task elicited a pattern of cardiovascular responding consistent with other more traditional passive stress tasks.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…First, the current passive stress task was successful in eliciting a notable cardiovascular stress response. Furthermore, participants' psychological experience of the task (in terms of PA, perceived stress, and anxiety) was no different to their experience during a well-established active stress task (Hughes & Callinan, 2007;O'Súilleabháin et al, 2018). Second, the task elicited a pattern of cardiovascular responding consistent with other more traditional passive stress tasks.…”
Section: Discussionmentioning
confidence: 89%
“…For the present study, forty neutral-emotion words, and forty negative-words, were chosen from the Affective Norms for English Words (ANEW; Bradley & Lang, 1999); a set of words rated in terms of valence (negative/positive emotions elicited) and arousal (high, low).Words were selected using previously reported cutoffs for arousal and valence; words were deemed negative if they had an arousal value greater than 6.00 and a valence value less than 4.00, and neutral if the arousal value was less than 5.45 and the valence value was between 4.00 and 6.00 (Scott, O'Donnell, Leuthold, & Sereno, 2009). This format of speech task has previously been shown to reliably elicit activity of the cardiovascular system (e.g., Hughes & Callinan, 2007;O'Súilleabháin, Howard, & Hughes, 2018).…”
Section: Stressor Tasksmentioning
confidence: 99%
“…As such, a naturally selected trait such as openness should be of crucial importance to an individual’s responsivity to stress experiences. As suggested by Ó Súilleabháin and colleagues [ 14 ] persons highest in openness should possess the required ability to stimulate short-term stress responsivity, while demonstrating an ability to habituate across time.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, when individuals are presented with similar stress exposures, patterns of cardiovascular stress adaptation have been observed (e.g., [ 29 , 30 ]). Recent research has also observed that patterns of cardiovascular adaptation can occur across a change in stress exposures [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the dynamics of these indices agreed with the behavioral effects of habituation. The intensity of habituation effects assessed by heart rate (HR) changes, systolic and diastolic pressure directly correlated with the indices of openness to a new experience evaluated on the basis of the questionnaire [7].…”
Section: Introductionmentioning
confidence: 99%